A De Novo heterozygous frameshift mutation identified in BCL11B causes neurodevelopmental disorder by whole exome sequencing. Issue 9 (25th July 2019) - Qiao, Fengchang; Wang, Chen; Luo, Chunyu; Wang, Yan; Shao, Binbin; Tan, Jianxin; Hu, Ping; Xu, Zhengfeng
Abstract: Background: Next‐generation sequencing has been invaluable to delineate the genetic etiology of neurodevelopmental disorders (NDDs) in recent years. BCL11B, encoding Cys2 His2 zinc finger transcription factor, is essential for the development of immune and neural systems. Methods: Herein, we describe a Chinese girl presenting craniofacial abnormalities, developmental delay and intellectual disability with speech impairment. Exomes of genes were enriched with the Agilent SureSelect QXT ALL Human Exon V6 kit and sequenced on Illumina Hiseq 2500 platform. Results: After variants filtering and annotation, we identified a de novo heterozygous 11bp frameshift mutation NM_138576.4: c.2190_2200delGGACGCACGAC (p.Thr730Thr fs *151) in exon 4 of BCL11B, which is expected to escape nonsense‐mediated mRNA decay and probably result in a truncated protein with lack of the C‐terminal DNA‐binding zinc‐finger domains. Conclusion: This is the first report of NDD caused by a BCL11B variant in a Chinese population. The mutation identified in this report broadens the knowledge of mutation spectrum of BCL11B and might help in genetic counseling and reducing reproductive risk. Abstract : We describe a Chinese girl presenting craniofacial abnormalities, developmental delay and intellectual disability with speech impairment. Using whole exome sequencing, we identified a de novo heterozygous 11bp frameshift mutation (c.2190_2200delGGACGCACGAC [p.Thr730Thr fs *151]) in exon 4 of BCL11B (NM_138576), which is expected to escape nonsense‐mediated mRNA decay and probably result in a truncated protein with lack of the C‐terminal DNA‐binding zinc‐finger domains.